2015
DOI: 10.15585/mmwr.mm6435a2
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Preparedness Knowledge and Beliefs on Household Disaster Preparedness

Abstract: Children Under 18 Years, a family of one adult and four children would need to have a household income of $25,625 or more to be above the poverty threshold. Any larger families would have a higher threshold. As the 2012 FEMA National Survey does not ask respondents about household size or number of children in the household, "less than $25,000 annually" serves as a proxy for low-income households.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 4 publications
5
43
0
6
Order By: Relevance
“…This finding is consistent with that reported from other studies that persons with more preparedness knowledge are more likely to have assembled an emergency kit. [42] Community disaster education programs may improve disaster knowledge, which in turn may influence preparedness behaviors. The UK Government distributed the Preparing for Emergencies booklet to each household in 2004.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with that reported from other studies that persons with more preparedness knowledge are more likely to have assembled an emergency kit. [42] Community disaster education programs may improve disaster knowledge, which in turn may influence preparedness behaviors. The UK Government distributed the Preparing for Emergencies booklet to each household in 2004.…”
Section: Discussionmentioning
confidence: 99%
“…Preparedness is motivated by perception of hazard effects capable of posing a threat [47]. Thomas et al [48] found that compared with persons with basic preparedness knowledge, persons with advanced knowledge were more likely to have assembled an emergency kit (44% versus 17%), developed a written household disaster plan (9% versus 4%), and received county emergency alert notifications (63% versus 41%).…”
Section: Threat Knowledge and Preparednessmentioning
confidence: 99%
“…According to the Center for Disease Control and Prevention (CDC), in the United States of America, disaster awareness is associated with household preparedness, which includes possessing an emergency kit [2]. Globally, campaigns have emphasized the importance of disaster kits.…”
Section: Introductionmentioning
confidence: 99%